2014
DOI: 10.4028/www.scientific.net/amm.563.215
|View full text |Cite
|
Sign up to set email alerts
|

Reliability Demonstration of a Robot System for an Unmanned Controlling Excavator

Abstract: This paper demonstrates reliability for an unmanned controlling excavator robot system under developing. A reliability testing method and testing devices were proposed using operation modes of excavators. Then, minimum MTBF of the system for a confidence level is demonstrated through results of the accelerated life test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Weibull distribution [32][33][34] and modifications of the Weibull distribution [35,36] for reliability analysis were discussed by several authors. Many researchers have suggested the lifetime distribution of the hydraulic excavator follows the Weibull distribution [37][38][39][40]; they stated above use Weibull distribution as theoretical reliability model, according to the experimental data, analyzed the reliability of the subsystems for the excavator. So the reliability goal of the new systems in this study is gained based on Weibull analysis.…”
Section: Proposed Comprehensive Methods For Reliability Allocationmentioning
confidence: 99%
“…Weibull distribution [32][33][34] and modifications of the Weibull distribution [35,36] for reliability analysis were discussed by several authors. Many researchers have suggested the lifetime distribution of the hydraulic excavator follows the Weibull distribution [37][38][39][40]; they stated above use Weibull distribution as theoretical reliability model, according to the experimental data, analyzed the reliability of the subsystems for the excavator. So the reliability goal of the new systems in this study is gained based on Weibull analysis.…”
Section: Proposed Comprehensive Methods For Reliability Allocationmentioning
confidence: 99%
“…In Beck et al, 7 the reliability of an unmanned controlling excavator robot system was verified. Mohammed and Athraa 8 examined nonlinear modelling of a fuzzy control design for a 4-DOF (degree of freedom) robotic backhoe excavator.…”
Section: Introductionmentioning
confidence: 99%
“…Gu et al 8 investigated various control systems for a robotic excavator, whose results demonstrated that state dependent parameter þproportional integral plus (SDP-PIP) controller can provide improved performance. However, current research mainly focus on the common excavator, [9][10][11][12] there are few reports about the research on the telescopic excavator, which has the greater flexible operation mode and the bigger operation range. So the research on spatial kinematics [13][14][15] of telescopic robotic excavator has significant value based on virtual prototype [16][17][18][19] and experiment research.…”
Section: Introductionmentioning
confidence: 99%